ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP KEBIJAKAN LAYANAN BANK SYARIAH INDONESIA KANTOR CABANG CUT MEUTIA - faris aulia; ayumiati ayumiati; akmal riza (Jihbiz: Global Journal of Islamic Banking and Finance., 2022)
The limited services of Bank Syariah Indonesia (BSI) during the pandemic resulted in various policies being carried out. The study aims to determine the impact of the Covid-19 pandemic on the service policy of the BSI Cabang Cut Meutia, and the obstacles in carrying out service policies during the pandemic. The study used primary data in the form of interviews with the parties concerned. Qualitative approach with descriptive analysis technique. The results of the research that the impact of Covid-19 on service policies are having to follow health protocols when entering the bank area, limiting operating hours, increasing e-Channel services, and following all stimulus policies issued by the government. The obstacles faced in the form of the implementation of the WFH system and the application of health protocols made employees feel uncomfortable and uncomfortable while working